Effects of clarithromycin treatment in scrub typhus in children: comparison with chloramphenicol and azithromycin - Min Lee; June Kim; Dae Sun Jo (Korean Pediatric Society, 2017)
PurposeChloramphenicol and tetracycline are not recommended for treating scrub typhus in pediatric patients because of potential side effects, such as aplastic anemia or tooth discoloration. While clarithromycin has recently been used in adults, few reports have been published on its effects in pediatric patients. We report the clinical profiles of pediatric scrub typhus and the effects of clarithromycin on scrub typhus in children.MethodsWe retrospectively analyzed medical records of 56 children with scrub typhus who were admitted between 2004 and 2013 to Chonbuk National University Hospital, Jeonju, Korea. Cases were divided into 3 groups based on thetreatment drug (chloramphenicol, azithromycin, and clarithromycin). We compared their clinical manifestations and laboratory findings.ResultsAll patients exhibited fever and rash. Other common clinical manifestations were eschars (66%), lymphadenopathy (48%), upper respiratory symptoms (42%), abdominal pain (32%), and hepatosplenomegaly (14%). Elevated levels of C-reactive protein, erythrocyte sedimentation rates, aspartate transaminase, and alanine transaminase were detected in 95%, 96%, 84%, and 77% of patients, respectively. Additionally, decreased platelet and white blood cell levels were observed in 43% and 36% of patients, respectively. There were no statistical differences between the treatment groups in mean age (P=0.114) or sex (P=0.507). However, time to defervescence after the treatments differed significantly, being the shortest in the clarithromycin group (P=0.019). All patients recovered without complications related to the disease or drugs.ConclusionClarithromycin was as effective as chloramphenicol and azithromycin in pediatric scrub typhus patients and may be used as a first-line treatment drug.